Maintenance Deep Transcranial Magnetic Stimulation Sessions are Associated with Reduced Depressive Relapses in Patients with Unipolar or Bipolar Depression - Rapinesi, Chiara; Bersani, Francesco Saverio; Kotzalidis, Georgios D.; Imperatori, Claudio; Del Casale, Antonio; Di Pietro, Simone; Ferri, Vittoria R.; Serata, Daniele; Raccah, Ruggero N.; Zangen, Abraham; Angeletti, Gloria; Girardi, Paolo (Frontiers in Neurology, 2015)
Introduction: Deep Transcranial Magnetic Stimulation (dTMS) is a new form of TMS allowing safe stimulation of deep brain regions. The objective of this perspective study was to assess the role of dTMS maintenance sessions in protecting patients with Bipolar Disorder (BD) or recurrent Major Depressive Disorder (MDD) from developing depressive or manic relapses in a 12-month follow-up period.Methods: 24 drug-resistant patients with a current depressive episode and a diagnosis of MDD or BD have been enrolled in the study. All the participants underwent daily dTMS sessions for 4 weeks. One group (maintenance – M - group) received additional maintenance dTMS sessions weekly or twice a week.Results: After the first dTMS cycle a significant reduction of HDRS scores was observed in all participants. Subsequently, the HDRS mean scores did not significantly change over time in the M group, while it significantly increased in the non M group after 6 and 12 months.Discussion: This perspective study confirms previous evidence of a positive therapeutic effect of dTMS on depressive symptoms and suggests that, after recovery from acute episodes, maintenance dTMS sessions may be helpful in maintaining euthymia in a 12-month follow-up period